Electronic structure and bond relaxation at Na/Ta(110) interfaces and 1D-chain and 2D-ring Ta metal structures on Na(110) - Bo, Maolin (2021)
We investigated the mechanism of Na/Ta(110) and Ta/Na(110) interfaces using a combination of bond band barrier (BBB) and zone selective electron spectroscopy (ZES) correlation. We found that 7/9 ML and 8/9 ML Ta metal on a Na(110) surface form one dimensional (1D) chain and two dimensional (2D) ring structures, respectively. Moreover, we show that on Na(110), the Ta-induced Na(110) surface binding energy (BE) shifts are dominated by quantum entrapment. On the contrary, on a Ta(110) surface, the Na-induced Ta(110) surface BE shifts are dominated by polarization. Thus, the BBB and ZES strategy could potentially be used for designing 1D and 2D metals with desired structures and properties.